Interpersonal conflicts in executive training: Types, antecedents and consequences. (May 2018) - Schermuly, Carsten C.; Schölmerich, Franziska
Executive training is an important part of leadership development, but little is known about interpersonal conflicts that can occur in leadership training. We conducted a qualitative ( N = 85) and quantitative ( N = 214) study to explore this new research field. With the help of these studies, we aim to identify typical interpersonal conflict types during executive training as well as their antecedents and consequences. The results of Study 1 show that the classic trichotomy of interpersonal conflicts should be extended for executive training. Besides task and process conflicts, two types of relationship conflicts occur in executive training: personal conflicts and status conflicts. Study 2 identified perceived subgroups as an antecedent and learning success as a consequence of interpersonal conflicts in executive training. While training-related task conflicts had a positive effect on learning success, relationship conflicts had a negative effect.